2020
DOI: 10.1097/aln.0000000000003164
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Fills for Lumbar Facet Radiofrequency Ablation Associated with New Persistent Opioid Use

Abstract: Background Zygapophyseal (facet) joint interventions are the second most common interventional procedure in pain medicine. Opioid exposure after surgery is a significant risk factor for chronic opioid use. The aim of this study was to determine the incidence of new persistent use of opioids after lumbar facet radiofrequency ablation and to assess the effect of postprocedural opioid prescribing on the development of new persistent opioid use. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The first study was conducted utilizing data obtained from the OptumInsight claims database. 24 , 25 The Clinformatics ™ Data Mart Database (OptumInsight, Eden Prairie, MN) is a de-identified database from a large national insurance provider. It includes commercial and Medicare Advantage claims data from ~83 million insured individuals, including inpatient, outpatient, prescription, geographic and socioeconomic details, and month of death for patients.…”
Section: Methodsmentioning
confidence: 99%
“…The first study was conducted utilizing data obtained from the OptumInsight claims database. 24 , 25 The Clinformatics ™ Data Mart Database (OptumInsight, Eden Prairie, MN) is a de-identified database from a large national insurance provider. It includes commercial and Medicare Advantage claims data from ~83 million insured individuals, including inpatient, outpatient, prescription, geographic and socioeconomic details, and month of death for patients.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of patients' general conditions, compared with patients without an opioid during hospitalization, patients with opioids had longer hospitalization days [9(7-10) days vs 8 (7)(8)(9)(10)(11)(12) days], and their disease duration was more than 1 month (84.0% versus 67.4%). The VAS score at admission was slightly higher [7(6-7) vs 6(5-6)], and the difference was considered statistically significant.…”
Section: Cohort Characteristicsmentioning
confidence: 99%
“…9 Since opioid crisis, with the deepening understanding of opioids, although a recent meta-analysis of randomized controlled trials ranging between 4 and 12 weeks concluded that some opioids could provide a short-term substantial pain relief in patients who suffer from postherpetic neuralgia and peripheral neuropathies of different aetiologies. 10 But in recent years, several studies had demonstrated that the new opioid exposure after surgery was a significant and independent risk factor for chronic opioid use, [11][12][13] and the long-term use might develop an opioid use disorder. 14 To date, opioid use had largely been used as a secondary outcome in most studies on ZRP, and few had evaluated both the improvement of pain degree and general quality of life in ZRP patients after opioid use.…”
Section: Introductionmentioning
confidence: 99%
“…Although adequate pain control is critical, surgeons now recognize the potential for misuse and long-term harms of opioids. [16][17][18][19][20][21][22][23][24][25][26][27] In ophthalmology, most attention has focused on prescription of opioids after incisional ophthalmic surgeries. Although best practices are becoming available for perioperative opioid prescribing, little is known about opioid prescribing in the nonperioperative setting.…”
mentioning
confidence: 99%
“…Although adequate pain control is critical, surgeons now recognize the potential for misuse and long-term harms of opioids. 16–27…”
mentioning
confidence: 99%